Design and Implementation of Web-Based Inventory Information System dengan Real-Time Stock Monitoring pada Gudang Perkebunan Kelapa Sawit - Ahmad Rohim; Indera (Jurnal Algoritma, 2026)
Warehouse inventory management in palm oil plantations requires a fast, accurate, and integrated system. Manual recording often causes stock discrepancies, delayed data updates, and weak inventory monitoring. This study aims to develop a Web-Based Inventory Information System to support real-time stock monitoring. The novelty of this study lies in automatic stock updates based on integrated inbound and outbound goods transactions with centralized reporting. The system was developed using the Waterfall method, UML design, web-based implementation, and Black Box Testing. The main features include item data management, inventory transactions, automatic stock updates, and inventory reports. Testing conducted on 25 scenarios showed that all functions operated according to requirements with a 100 percent success rate. This system is capable of improving inventory management efficiency, accelerating stock monitoring, reducing recording errors, and supporting data-driven decision-making.